Digital Pedagogy in Islamic Education: A Systematic Review Toward a Value-Inclusive Framework - Yuliana Yuliana; Tri Wahyudi Ramdhan; Rafat Bukola Dauda (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2026)
This study examines the transformation of digital pedagogy in Islamic education by addressing the tension between technological integration and the preservation of value-based learning traditions. Using a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol, this study analyzes 20 peer-reviewed journal articles published between 2021 and 2025. The analysis combines thematic content analysis and critical interpretation to identify technological typologies, implementation challenges, and adaptive strategies. The findings reveal that digital pedagogy in Islamic education is characterized by a hybrid model that integrates technologies such as Learning Management Systems (LMS) and communication platforms, as well as emerging tools such as artificial intelligence, without replacing traditional pedagogical practices. However, the study also identifies significant limitations of digital systems in facilitating the transmission of ethical and spiritual values, highlighting the continued centrality of teacher presence. In addition, the transformation of religious authority and institutional governance emerges as a key dimension of digitalization. This study contributes to the literature by proposing a value-inclusive digital pedagogical framework, which integrates technological, pedagogical, and ethical dimensions. The findings imply that effective digital transformation in Islamic education requires a balanced approach that aligns technological innovation with core values such as adab and barakah.